Justification of Surah An-Nisa, Verse 34 Regarding the Wifes Defeatist Attitude Toward Domestic Violence (DV) - Ilmiy Anillah Maula; Siti Ayu Rahayu (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Domestic Violence (KDRT) is a conscious act that occurs within the family sphere and causes both physical and psychological suffering to its victims, who are predominantly women. One of the common factors contributing to such acts is the misinterpretation of certain Islamic teachings, which are often misunderstood and misused. In reality, a thorough examination shows that domestic violence is an act that clearly violates the principles of Islamic law, as Islam is a religion grounded in egalitarian values, justice, and public welfare, upholding human dignity—including the elevation of womens status and honor. In this regard, a serious and accurate understanding of Islamic legal interpretations related to family relationships is necessary as an assertive stance and a preventive effort against the normalization of wives submissiveness in the face of abuse. This requires a comprehensive study and understanding based on both the Quran and Hadith as foundational references for developing a more representative and forward-looking paradigm.